GE_GERICHTE P/5763/2025 vom 14. April 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ESCROQUERIE;CHOSE CONFIÉE;ABUS DE CONFIANCE;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) | CPP.310; CP.146; CP.138; CP.144; CC.715; CC.714